Le mastaba E17 et la nécropole de l'Ancien Empire - Ziegler, Christiane, (Fouilles du Louvre a Saqqara ;, 2022)
This third volume in a series devoted to the excavations of the Louvre Museum in Saqqara studies the tombs of the Old Kingdom discovered under the direction of Christiane Ziegler. Around the mastaba of Akhethetep, now kept in the Louvre and published in volume I, unfolds a necropolis hitherto unknown with the exception of the small decorated chapel E17 excavated by Mariette. It is a series of stone and brick mastabas whose excavation has revealed the topography and the history of this northern zone of the Unas causeway at the time of the pyramids. The sector has delivered burials as well as numerous objects from the same period: fragments of bas-reliefs, stelae, offering tables, items of funerary furniture, ceramics. The scientific presentation of the results is accompanied by a series of multidisciplinary studies on geophysical prospecting, hieratic inscriptions and graffiti, human remains, ceramics, mud bricks and their modules, preventive conservation and restoration. The carbon 14 analysis carried out on the samples taken during the excavations provide details on the chronology of the Old Kingdom.